The Students Perception on The Service Quality of Primary Teacher Education (PGSD) in Faculty of Teacher Training And Education (FKIP) of Tanjungpura University (UNTAN) - Suhardi Marli (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2019)
The problem in this study was "How is the quality of service in the FKIP Untan PGSD study program that focuses on the problem: (1) how is the perception of PGSD students in academic guidance (PA)?; (2) how is academic service in PGSD ?; (3) what is the service of library staff at PGSD?; the purpose of the research is to find out: the perceptions of students on academic guidance, academic services at PGSD ?; and library staff services at PGSD. The place of research was conducted at PGSD. The subjects of the study were PGSD students in 2014, amounting to 180 people in the third semester and semester five students receiving the Bidik Misi scholarship. His research was in the form of a survey with a data collection tool used in the questionnaire and interview sheet. The results of the study are: (1) the role of the academic advisory service (PA) places the category well in the top position, namely 57, 41%, the category is very good (SB) at the second position which is 22.10%, enough in the third position 17.52% and less fourth position 2.96%. (2) the role of academic services places a good (B) category at the top position, namely 53.21%, while the excellent category places the second position which is 32.21%, enough in the third position 17.52% and less in the fourth position 2.96%. (3) the category of library service roles. The category of good at the top position is 45.47% while the excellent position occupies the second position 15.25%, enough in the third position 26.10% and less in the fourth position which is 12.92%, with the general conclusion that the Academic Advisor services (PA ), academic services and library services at PGSD are included in the good (B) category.